Analysis of flavor formation during the production of Jinhua dry-cured ham using headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). (December 2022) - Li, Ping; Zhou, Hui; Wang, Zhiqi; Al-Dalali, Sam; Nie, Wen; Xu, Feiran; Li, Cong; Li, Peijun; Cai, Kezhou; Xu, Baocai
Abstract: This study aimed to clarify the formation process of flavor compounds and identify the volatile substances present during a continuous period of Jinhua dry-cured ham (JDH) making. Via headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS), a total of 53 volatile organic compounds (VOCs), including 20 aldehydes, 16 alcohols, 11 ketones, 5 esters and 1 furan, were identified in JDH from seven sampling stages. The results showed that butanal, 3-methylbutanal, 2-methylbutanal, 2-hexanone, 2-pentanone and 2-butanone could be flavor markers in the evolution of aroma characteristics of JDH. Aldehydes (2-methylbutanal and 3-methylbutanal), alcohols (2-methylpropanol, 2-methylbutanol, 3-methylbutanol and 1-penten-3-ol), ketones (2-pentanone, 2-propanone, 2-butanone and 2-hexanone) and esters (ethyl acetate and ethyl 3-methylbutyrate) were considered the main VOCs in the mature JDH. Free fatty acid (FFA) analysis displayed the changes in intramuscular fat (IMF) of JDH. Additionally, principal component analysis (PCA) showed that drying-ripening was a critical stage in the flavor formation of JDH. Highlights: A total of 53 volatile compounds in JDH were identified via HS-GC-IMS. Changes in flavor compounds and FFAs of JDH during processing were evaluated. Salting plays a critical role in the preparation flavoring precursors. Drying-ripening plays a critical role in the formation of flavor.